2013
DOI: 10.1155/2013/602981
|View full text |Cite
|
Sign up to set email alerts
|

Methadone-Induced Toxic Brain Damage

Abstract: A 29-year-old man presented with comatose after methadone intoxication. Cerebral tomography only showed cortico-subcortical hypodense signal in the right cerebellar hemisphere. Brain MRI showed a rare imaging of FLAIR and DWI hyperintensities in the two cerebellar hemispheres as well as basal ganglia (globi pallidi), compatible with methadone overdose. To our knowledge this is the first reported case of both cerebellar and basal ganglia involvement in methadone overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 4 publications
5
26
0
Order By: Relevance
“…Involvement of the basal ganglia is also noticed in a few of these cases 6. A similar explanation may be given in cases of alcohol intoxication.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Involvement of the basal ganglia is also noticed in a few of these cases 6. A similar explanation may be given in cases of alcohol intoxication.…”
Section: Discussionsupporting
confidence: 58%
“…These were likely due to reduced brain perfusion 6. These lesions were bilaterally symmetrical, and the distribution of the affected areas was highly indicative of a toxic injury 6. Bilateral involvement of the basal ganglia and thalami has been reported in a few cases of ethylene glycol intoxication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a cerebellar and basal ganglia involvement in methadone overdose as well [Corre et al, 2013]. Euphoria, slurred speech and ataxia were the most common initial symptoms of severe methadone poisoning [Caplehorn,1998].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Li et al (2016) suggested that methadone damages the integrity of the white matter of long‐time consumer of methadone in a dose‐dependent pattern . The radiological studies revealed that methadone in high concentration and long‐term consumption influences on the structure of the brain in the cerebellum, basal ganglia, and deep white matter of the cerebral hemispheres . For methadone, two signal paths have been suggested: one for binding to opioid receptors and another for acting as an antagonist in NMDR .…”
Section: Resultsmentioning
confidence: 99%